Complex palaeo-ice sheet dynamics in northeast Ireland during the retreat and reorganisation of the central British-Irish Ice Sheet - Alexander M. Clark; Bethan J. Davies; Sam Roberson; Simon P.E. Blockley; Adrian P. Palmer; Magret Damaschke (Geomorphology, 2026)

Refining the known extent of major onshore Quaternary glaciation in the UK — Types of evidence, nomenclature and uncertainty - Jonathan R. Lee; Sam Roberson (Proceedings of the Geologists' Association, 2025)

Capturing exposed bedrock in the upland regions of Great Britain: A geomorphometric focused random forest approach - Chris Williams; Katie Whitbread; Alex Hall; Sam Roberson; Andrew Finlayson; Romesh N. Palamakumbura; Andrew Hulbert; Matthew Paice (Computers & Geosciences, 2025)

Younger Dryas glaciers and climate in the Mourne Mountains, Northern Ireland - Iestyn D. Barr; Sam Roberson; Rory Flood; Jason Dortch (Journal of Quaternary Science, 2017)
Here, we present evidence to suggest that the Mourne Mountains, Northern Ireland, were last occupied by glaciers during the Younger Dryas Stadial. The margins of these glaciers are marked by moraines, chronologically constrained to the Younger Dryas by Schmidt hammer exposure dating. Reconstructions indicate that these glaciers had equilibrium‐line altitudes (ELAs) ranging from 356 ± 33 m (a.s.l.) to 570 ± 9 m (a.s.l.), with a mean of 475 ± 36 m (a.s.l.). ELAs rise from west to east, probably reflecting the contribution of windblown snow and ice to the accumulation of Younger Dryas glaciers in the western Mournes. Taking this into consideration, a mean ‘climatic’ ELA of 529 ± 4 m (a.s.l.) is calculated for the mountains as a whole. Assuming a mean annual sea level air temperature of −8 °C, and an annual temperature range of 34 °C, degree‐day modelling suggests that during the Younger Dryas, accumulation at the ‘climatic’ ELA of glaciers in the Mournes was 846–990 mm a −1 . This suggests increased aridity, relative to present, and is consistent with other parts of NW Europe, where reduced precipitation alongside notable cooling is thought to reflect increased North Atlantic sea ice extent during the Younger Dryas.